Effect of Tai Chi combined with music therapy on the cognitive function in older adult individuals with mild cognitive impairment - Zhou, Chunhui (Frontiers in Public Health, 2025)
BackgroundWith the global aging population increasing, cognitive impairment among the older adult, particularly Mild Cognitive Impairment (MCI), has garnered remarkable attention. MCI, often a precursor to dementia, presents an opportunity for early intervention. This study investigates the effects of Tai Chi combined with music therapy on the cognitive function in older adult individuals with MCI.MethodsIn this randomized controlled trial, 66 older adult participants with MCI were randomly assigned to one of the following three groups: a Control Group (CG), a Tai Chi Group (TCG), and a Tai Chi Combined with Music Group (TCMG), with 22 participants in each group. Cognitive function was evaluated over a 12-week intervention using the Montreal Cognitive Assessment (MoCA), Mini-Mental State Examination (MMSE), and Stroop Color and Word Test.ResultsBaseline characteristics showed no significant differences among the groups. The TCG and TCMG exhibited significant improvements after 16-week intervention. The participants with TCG group improved in MoCA score (P = 0.005), attention accuracy (P = 0.031), and delayed recall (P = 0.003). The participants with TCMG showed notable enhancements in MoCA (P = 0.000), MMSE (P = 0.001), attention accuracy (P = 0.025), visuospatial and executive functions (P = 0.001), naming (P = 0.014), abstraction (P = 0.020), and delayed recall (P = 0.006). The CG experienced decreased language repetition ability (P = 0.042) and delayed recall (P = 0.030).ConclusionTwelve weeks of Tai Chi combined with music therapy substantially improved cognitive function in older adult individuals with MCI. This combined intervention is more effective than Tai Chi alone, highlighting its potential as a non-pharmacological approach to enhance cognitive health in the aging population.